Evaluation of the 2012 Drought with a Newly Established National Soil Monitoring Network. Issue 11 (30th October 2015) - Bell, Jesse E.; Leeper, Ronald D.; Palecki, Michael A.; Coopersmith, Evan; Wilson, Tim; Bilotta, Rocky; Embler, Scott
Abstract : Core Ideas: New US soil moisture network provides new opportunity to evaluate drought Soil moisture at deeper depths did not fully recover from the 2012 drought in 2013 Soil moisture varied by region in the response to drought The NOAA United States Climate Reference Network (USCRN) deployed soil moisture sensors during 2009 to 2011 to monitor the temporal and spatial variability of soil moisture at 114 locations in the contiguous United States. These new soil observations will enhance our understanding of changing soil conditions for better drought monitoring. One year after full deployment of the network, a large drought occurred across most of the United States and provided an opportunity to evaluate the utility of this network for drought monitoring. The soil moisture signal of the 2012 drought in the continental United States was detected nationally at all observational depths (5, 10, 20, 50, and 100 cm), with an overall 11.07% decrease from the average of the 2011 to 2013 summers. The top three depths (5, 10, and 20 cm) experienced the largest decrease in soil moisture. Although 2013 national precipitation totals returned to normal values and national soil moisture levels recovered from the 2012 drought, the national average soil moisture concentrations combined at the 50‐ and 100‐cm depths remained around 18% below pre‐drought levels. Regional analysis of the 2012 drought identified that the Upper Midwest, Northeast, Northern Rockies and Plains, and Ohio Valley climate regions were most impacted and demonstrated a temporal pattern similar to the national analysis. These results demonstrate the utility of using USCRN for monitoring national soil moisture conditions, assessing droughts, and tracking climate change with time.